Beneath the Bark: Assessing Woody Stem Water and Carbon Fluxes and Its Prevalence Across Climates and the Woody Plant Phylogeny - Berry, Z. Carter; Ávila-Lovera, Eleinis; De Guzman, Mark E.; O’Keefe, Kimberly; Emery, Nathan C. (Frontiers in Forests and Global Change, 2021)
While woody stems are known to influence carbon and water dynamics, direct exchange with the atmosphere is seldom quantified, limiting our understanding of how these processes influence the exchange of mass and energy. The presence of woody stem chlorophyll in a diversity of climates and across a range of species suggests an evolutionary advantage to sustaining carbon assimilation and water relations through permeable stem tissue. However, no formal evaluation of this hypothesis has been performed. In this mini-review, we explore the interactions between woody stems and the atmosphere by examining woody stem photosynthesis and bark-atmosphere water exchange. Specifically, we address the following questions: (1) How do water and carbon move between the atmosphere and woody stems? (2) In what climate space is woody stem photosynthesis and bark water uptake advantageous? (3) How ubiquitous across plant families is woody stem photosynthesis and bark-atmosphere water exchange? In the literature, only seven species have been identified as exhibiting bark water uptake while over 300 species are thought to conduct woody stem photosynthesis. The carbon dioxide and water gained from these processes can offset respiration costs and improve plant water balance. These species span diverse biomes suggesting a broad prevalence of bark-atmosphere permeability. Finally, our results demonstrate that there may be an evolutionary component as demonstrated by a high Pagel’s lambda for the presence of stem photosynthesis. We end with recommendations for future research that explores how bark water and carbon interactions may impact plant function and mass flow in a changing climate.